PERAN PROGRAM PELATIHAN DAN PENGEMBANGAN KERJA GUNA MENINGKATKAN KINERJA DAN PRODUKTIVITAS DI PT. SURYA PERTIWI NUSANTARA - Ilyas Indra; hafidz ahmad hidayatulloh; Yudhitia Dian Putra (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
ABSTRACT This research was conducted with the aim of knowing (1) the frequency of significant changes in performance and employee productivity at PT. Surya Pertiwi Nusantara before and before the implementation of training and development activities, (2) influence and development on the performance and productivity of employees at PT. Surya Pertiwi Nusantara. This research is a descriptive survey research. Data collection techniques were carried out through interviews, filling out questionnaires, observation and document studies. The data were analyzed using the Mc Nemar Change test to determine the significance of the changes. The results showed that (1) the frequency of significant changes in employee performance and productivity at PT. Surya Pertiwi Nusantara showed a significant change with low productivity of 1 person, no increase in productivity of 10 people, and no increase in productivity of 3 people, (2) there was a positive effect of training and development activities on employee performance and productivity at PT. Surya Pertiwi Nusantara is proven by the value of Sig. (2-tails) 0.006 < 0.05.